2018
DOI: 10.1128/aac.01092-18
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetic Model and Limited Sampling Strategies for Personalized Dosing of Levofloxacin in Tuberculosis Patients

Abstract: Levofloxacin is an antituberculosis drug with substantial interindividual pharmacokinetic variability; therapeutic drug monitoring (TDM) could therefore be helpful to improve treatment results. TDM would be more feasible with limited sampling strategies (LSSs), a method to estimate the area under the concentration curve for the 24-h dosing interval (AUC0–24) by using a limited number of samples. This study aimed to develop a population pharmacokinetic (popPK) model of levofloxacin in tuberculosis patients, alo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 31 publications
0
20
0
1
Order By: Relevance
“…For these reasons, we expect the results reported here to represent the clinical practice of TDM using these LSSs very closely. The small sample size of the MFXϩRIF group can be considered a limitation as well, although comparable to previously published LSS studies (21,(37)(38)(39)(40). We consider this sample size to be sufficient for exploratory objectives, since this is the first study that…”
mentioning
confidence: 66%
“…For these reasons, we expect the results reported here to represent the clinical practice of TDM using these LSSs very closely. The small sample size of the MFXϩRIF group can be considered a limitation as well, although comparable to previously published LSS studies (21,(37)(38)(39)(40). We consider this sample size to be sufficient for exploratory objectives, since this is the first study that…”
mentioning
confidence: 66%
“…The simple and multiple regression equations for estimating AUC 0-12h with good correlation r 2 were shown in Table 5. C 2h model and all models using two to four samples met the acceptance criteria (Van den Elsen et al, 2018;Zhang et al, 2018). With the increase of sample points, the linear correlations between predicted and measured AUC 0-12h were improved.…”
Section: Limited Sampling Strategymentioning
confidence: 87%
“…3) were used to evaluate the accuracy and precision of the model. The acceptance criteria of RMSE < 15 and r 2 > 0.95 (Van den Elsen et al, 2018).…”
Section: Limited Sampling Strategiesmentioning
confidence: 99%
“…Developed limited sampling strategies have shown that single or multiple samples collected after drug administration can be used to quantify levofloxacin exposure, which mitigates the risk of interference. 39 …”
Section: Discussionmentioning
confidence: 99%